2016
DOI: 10.1111/jfpp.12808
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Properties of Extruded Copolymer Film

Abstract: The aim of this study was to investigate the properties of copolymer films made from cassava starch and jellyfish gelatine with glycerol or sorbitol as a plasticizer. The concentrations of gelatine used were 1 and 3% (wt/vol). The prepared copolymer of cassava starch solution (5%) and gelatine solution (1:1 (vol/vol)) was mixed with glycerol or sorbitol (30%) prior to extrusion. The feeding rate of solution was 1 kg/h and the extruder screw speed was 30 rpm. The films were dried by an infared dryer. All extrud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…In this study, no bleaching step was applied during extraction. The color was similar to the sample of type A jellyfish gelatin that appeared in yellow shades that were reported earlier [ 21 ].…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In this study, no bleaching step was applied during extraction. The color was similar to the sample of type A jellyfish gelatin that appeared in yellow shades that were reported earlier [ 21 ].…”
Section: Resultssupporting
confidence: 85%
“…Apart from application in food products, jellyfish gelatin is applied in film formation. Extruded copolymer film composed of 3% jellyfish gelatin and 5% cassava starch solution showed that elongation of glycerol plasticized film increased greater than that of sorbitol plasticized film [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher OTR values of films containing 40%–50% sorbitol compared to films containing 40%–50% glycerol may reflect the presence of randomly placed micro‐cracks, which would increase the permeability to oxygen as well as water vapor. Thumthanaruk et al [ 32 ] showed that the glycerol and sorbitol content of all copolymer films had no significant effect ( p ≥ 0.05) on OTR values, but concluded that bubbles and bumps may influence the oxygen permeability. McHugh and Krochta [ 33 ] concluded that the oxygen permeability of sorbitol films was lower than that of glycerol films, despite the higher sorbitol concentration.…”
Section: Resultsmentioning
confidence: 99%